Current Evidence for a Role of the Kynurenine Pathway of Tryptophan Metabolism in Multiple Sclerosis - Lovelace, Michael D.; Varney, Bianca; Sundaram, Gayathri; Franco, Nunzio F.; Ng, Mei Li; Pai, Saparna; Lim, Chai K.; Guillemin, Gilles J.; Brew, Bruce J. (Frontiers in Immunology, 2016)
The kynurenine pathway (KP) is the major metabolic pathway of the essential amino acid tryptophan (TRP). Stimulation by inflammatory molecules such as interferon-γ (IFN-γ) is the trigger for induction of the KP, driving a complex cascade of production of both neuroprotective and neurotoxic metabolites and in turn, regulation of the immune response and responses of brain cells to the KP metabolites. Consequently, substantial evidence has accumulated over the past couple of decades that dysregulation of the KP and the production of neurotoxic metabolites are associated with many neuroinflammatory and neurodegenerative diseases, including Parkinson’s disease, AIDS-related dementia, motor neurone disease (MND), schizophrenia, Huntington’s disease and brain cancers. In the past decade, evidence of the link between the KP and multiple sclerosis (MS) has rapidly grown and has implicated the KP in MS pathogenesis. KP enzymes indoleamine 2,3-dioxygenase (IDO-1) and tryptophan dioxygenase (TDO; highest expression in hepatic cells) are the principal enzymes triggering activation of the KP to produce kynurenine from TRP. This is in preference to other routes such as serotonin and melatonin production. In neurological disease, degradation of the blood-brain-barrier (BBB), even if transient, allows the entry of blood monocytes into the brain parenchyma. Like microglia and macrophages, these cells are highly responsive to IFN-γ, which upregulates the expression of enzymes including IDO-1, producing neurotoxic KP metabolites such as quinolinic acid (QUIN). These metabolites circulate systemically or are released locally in the brain, and can contribute to the excitotoxic death of oligodendrocytes and neurons in neurological disease principally by virtue of their agonist activity at NMDA receptors. The latest evidence is presented and discussed. The enzymes that control the checkpoints in the KP represent an attractive therapeutic target, and consequently several KP inhibitors are currently in clinical trials for other neurological diseases, and hence may make suitable candidates for MS patients. Underpinning these drug discovery endeavours, in recent years several advances have been made in how KP metabolites are assayed in various biological fluids, and tremendous advancements have been made in how specimens are imaged to determine disease progression and involvement of various cell types and molecules in MS.